Marriage impediments resulting from dignity of the human - KRAJCZYŃSKI, JAN (Prawo Kanoniczne, 2012)
At first, the author of the paper presents some selected aspects of Catholic doctrine on human dignity. He focuses on two issues, which are respectively: 1) dignity of the human and the Christian marriage; 2) law on marriage impediments and the human dignity. Still, the analysis of respective impediments to marriage resulting from the dignity of the human was actually limited to two following problems: 1) human dignity and legal norms on specific impediments; 2) observations of pastoral, administrative or procedural nature that should be taken into account when settling certain issues of the relevant marriage impediment. Critical analysis of the issue allows to put forward the following conclusions: The evolution of canonical discipline in terms of the analyzed three marriage impediments resulting from the human dignity means more efficient, complete and clear protection of human dignity and human rights. Development of above mentioned protection is indicated by the following: giving the unconditional nature to the impediment of age, extending the scope of impediment when the woman has been abducted with her being forcefully detained, reducing the misdemeanor impediment to these cases in which the death of the spouse actually takes place. Although the binding law successfully protects both the dignity and subjective rights of the human, still the further and permanent reflection on values engrained in the human being’s nature are highly desired to be maintained so that the very inalienable dignity and transcendent destiny may be always respected. Administering the law, no matter who shall do it, cannot be distinguished by its interpretation – even though it would be due to most humanitarian reasons – that would do harm either to a legal norm or to the human dignity. In other words, all legal regulations, also the ones relating to marriage impediments, need to be always interpreted in line with the legislator’s intention and applied with equity.